Articulate necrographies: comparative perspectives on the voices and silences of the dead - Panagiotopoulos, Anastasios; Espírito Santo, Diana (Berghahn, 2019)
Going beyond the frameworks of the anthropology of death, Articulate Necrographies offers a dramatic new way of studying the dead and its interactions with the living. The collection introduces the concept of "necrography" to describe the way death and the dead create their own kinds of biographies in and among the living.